EVALUATION OF TWO VACCINATION PROGRAMS USING THE INFECTIOUS BURSAL DISEASE 2512 STRAIN AGAINST EXPERIMENTAL INFECTION WITH THE F52/70 STRAIN - Pérez C., Claudia (2008)
The objective of the present study was to evaluate the immunoprotection given by two vaccination programs in broilers, using comercial vaccines against the infectious bursal disease virus (IBDV). In group A, the strain 2512 (intermediate plus) was inoculated at 19 days of age; in group B was used two intermediate-intermediate vaccines: the strain 2512 at day 10 and the strain 228TC at day 19; and group C was used as the nonvaccinated control group. The three groups were challenged at day 32 with the standard strain F52/70 of IBDV. The protection was measured after the challenge through clinical signs (diarrhea), size of the bursa, bursal index, productive parameters and antibody titers. The size and the bursal index at 7 days post challenge in the three groups showed bursal atrophy but this, did not significantly affect productive parameters. Groups A and B had similar body weights and antibody titers at day 49 (p>0.05). The results obtained in bursal damage, histopathology, bursal index, productive parameters, and antibody titers indicated that chicks of groups A and B were protected against the IBDV strain of challenge.